Dissolved and particulate carbon and nitrogen fluxes along a Phytophthora agathidicida infection gradient in a kauri (Agathis australis) dominated forest. (December 2019) - Schwendenmann, Luitgard; Michalzik, Beate
Abstract: Kauri dieback, caused by Phytophthora agathidicida, is an emergent threat to the ecologically unique and carbon-rich kauri ( Agathis australis ) forests in New Zealand. Our main aim was to assess the effect of kauri dieback on canopy and forest floor dissolved and particulate carbon (C) and nitrogen (N) fluxes. Throughfall and stemflow collectors and free-draining lysimeters were deployed underneath the canopy of ten kauri trees differing in their soil P. agathidicida DNA concentration and visual health status and sampled weekly to monthly over 1 y. Throughfall and forest floor dissolved C and N fluxes decreased significantly with increasing soil P. agathidicida DNA concentration which may be related to changes in leaf chemistry, leachable kauri leaf surface area and uptake of N by the understory vegetation. The observed alteration in dissolved and particulate C and N fluxes under P. agathidicida infected kauri trees could lead to long-term changes in biogeochemical processes (e.g. mineralization, nutrient availability) in these ecologically unique kauri forests.